PERAN KELOMPOK WANITA TANI (KWT) DALAM MEMBANTU PEREKONOMIAN KELUARGA DI DESA PURWODADI LAMPUNG TENGAH - Suprihatin, Yeni; Dartiara, Rika (Jurnal Studi Gender dan Anak, 2021)
This study aims at describing the role of farmer women community in improving the family income located in Purwodadi Central lampung. KWT as the solution of the problems which certainly can help in the field of the welfare of family. Descriptive design was used in this research. The researcher determined the informants by using purposive sampling technique with the number of informants 12 people. The type of data used is primary data and secondary data. Data collection techniques were collected through the triangulation methods such as observation (non-participant), in-depth interviews and questionnaire. The result of the data indicated that the farmer women can be both the independent women and the fully housewives. By joining the farmer women community, they could earn of farming to help their husband and to meet the needs of family.